Anlagen- und Prozeßdiagnostik beim Schneiden mit einem gepulsten Nd:YAG-Laser - Gropp, Armin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1995)
The aim of this thesis has been to improve the process understanding for the manufacturing method cutting with pulsed Nd:YAG-lasers. To view this topic in its entirety diagnostic examination has been carried out in the entire working system and during the process. Optical signals emitted by the process have been registered by means of different detectors. The analysis of the signals shows that the interaction is usually connected with laser pulse duration. Therefore irregular courses of some signals can be used to monitor the process. Three dimensional cutting courses show that the extent of accuracy of the work piece is dominated by the guiding behavior of the robot. However, any influence of gravity on the process could not be found. The pulsed mode and the low mean power of the laser are advantageous when working on complex contours because of a low susceptibility of the process and with it the working quality with regard to a drop of the cutting speed below optimal value